Complications of prostate biopsy. Issue 7 (July 2013) - Anastasiadis, Anastasios; Zapała, Łukasz; Cordeiro, Ernesto; Antoniewicz, Artur; Dimitriadis, Georgios; De Reijke, Theo
Biopsy of the prostate is a common procedure with minor complications that are usually self-limited. However, if one considers that millions of men undergo biopsy worldwide, one realizes that although complication rate is low, the number of patients suffering from biopsy complications should not be underestimated and can be a clinically relevant problem for healthcare professionals. In this review, the authors present diagnosis and management of postbiopsy of prostate complications. Bleeding is the most common complication observed after prostate biopsy, but the use of aspirin or nonsteroidal anti-inflammatory drugs is not an absolute contraindication to prostate biopsy. Emerging resistance to ciprofloxacin is the most probable cause of the increasing risk of infectious complications after prostate biopsy. Even though extremely rare, fatal complications are possible and were described in case reports.